Damage identification and seismic vulnerability assessment of a historic masonry chimney - Masciotta, Maria Giovanna (2017)
The present paper deals with the dynamic characterisation of a historical masonry chimney aimed at identifying the structural damage and assessing its seismic performance. The structure was severely damaged by a lightning accident and in-depth repair works were executed to re-instate its sound configuration. The case study is fully detailed, including the aspects of survey, inspection, diagnosis, and evolution of the dynamic properties of the system throughout the structural intervention. Considering the explicit dependence of the power spectral densities of measured nodal processes on their frequency content, a spectrum-driven algorithm is used to detect and locate the damage. The paper shows that the eigenparameters obtained from the decomposition of the response power spectrum matrix are sensitive to system's changes caused by evolutionary damage scenarios, thereby resulting excellent indicators for assessing both the presence and position of structural vulnerabilities. The results are compared with the ones from other modal-based damage identification methods and the strengths/limitations of the tools currently available in literature are extensively discussed. Finally, based on the crack pattern surveyed before the repair works, the weakest links of the chimney are identified and the most meaningful collapse mechanisms are analysed to verify the seismic capacity of the structure. According to the results of the kinematic analysis, the chimney does withstand the maximum site peak ground acceleration.